The Effect of Broad-Spectrum Dietary Supplementation on Quality of Life, Symptom Severity, and Functioning in Multiple Sclerosis. (1st November 2020) - McDaniel, H. Reginald; LaGanke, Christopher; Bloom, Laura; Goldberg, Sharon; Hensel, Judith; Lantigua, Laura A.; Lages, Lucas C.; Atlas, Steven E.; Woolger, Judi M.; Lewis, John E.
Abstract: Multiple sclerosis (MS) is a progressive neurodegenerative disease that exerts a significant quality-of-life toll on patients. According to the literature, broad-spectrum dietary supplementation including a variety of nutrients, polysaccharides, and compounds may improve the quality of life, functionality, and symptom severity in people with MS. Individuals ( n  = 15) diagnosed with relapsing-remitting MS (RRMS) for an average of 12.4 years (SD = 7.4; R = 2, 25) were enrolled in a one-year open-label clinical trial in which they consumed a broad-spectrum dietary supplement regimen three times daily. Participants were assessed at baseline and at 3, 6, 9, and 12 months with the following: (1) Functional Assessment of MS (FAMS), (2) the EQ-5D-3L, (3) Beck Depression Inventory-II (BDI), (4) Health Conditions Discomfort Scale (HCDS), and (5) Self-Assessment of Severity of MS Symptoms Scale (SASMSSS). Participants included seven females and eight males (M age = 51.3 years; SD = 7.2; R = 38, 65). Few minor gastrointestinal effects were reported. At the end of the intervention, participants showed significant improvements in all outcome measures, particularly functionality on the FAMS, overall quality of life on the EQ-5D-3L, fewer depressive symptoms on the BDI, and improved severity of symptoms on the HCDS and the SASMSSS. Our results suggest that dietary supplementation containing a variety of nutrients can improve the quality of life, severity of disease symptoms, and functionality in MS patients. These findings are clinically promising for MS patients, given the lack of treatment options geared toward improving quality of life in this population.